Bangladesh: proyecto SHAHAR - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
IFPRI is collaborating with CARE-Bangladesh to provide research and support for its SHAHAR project for improving urban livelihoods. This Country Report addresses the research focus, under Project Leader, James Garrett, and the key findings and the impacts of the program.